PATTERN OF SEXUALLY TRANSMITTED INFECTIONS IN MALES IN INTERIOR SINDH: A 10-YEAR-STUDY - Bhutto, Abdul Manan; Shah, Aftab Hussain; Ahuja, Dileep Kumar; Solangi, Aijaz Hussain; Shah, Sharaf Ali (Journal of Ayub Medical College Abbottabad, 2011)
Background: Sexually transmitted infections (STIs) are widespread in Pakistan and have not been fully documented particularly in Sindh Province. The aim of this study is to determine the number and clinical pattern of various types of STIs in general population of Larkana division and its surrounding cities. Methods: A hospital based prospective study was carried out at Male-STD-Clinic in the Department of Dermatology, Shaheed Muhtarma Benazir Bhutto Medical University Hospital Larkana from January 2000 to December 2009. Results: Among 4,288 patients, 3,947 (92.04%) had the history of extra marital sexual contact and simultaneously had developed the clinical signs of STIs; 341 (7.95%) had history of extra marital sexual contact but did not have the manifestation of STIs. Majority of the patients (3,860, 90.01%) had the history of heterosexual contact with different partners, but only few 171 (3.98%) of them had the history of homosexual contact. According the syndromic diagnosis 1930 (45.00%) patients had genital ulcer (including herpes genitals) with or without skin manifestations, 690 (16.09%) had urethral discharge, 431 (10.05%) had genital warts, 349 (8.14%) had lesions other than STIs related, 304 (7.08%) had more than one syndrome, 193 (4.50%) had scrotal swelling, 46 (1.07%) had inguinal bubo, 3 (0.06%) were human immunodeficiency virus (HIV) positive, and 1 (0.02%) had ophthalmia neonatorum. Based on the clinical and etiological grounds: 2560 (59.70%) had syphilis, 640 (14. 92%) had gonorrhoea, 399 (9.30%) had mixed infections, 40 (0.93%) had chancroid, 431 (10.05%) had genital warts, 40 (0.93%) had lymphogranuloma venerum (LGV) and granuloma inguinale (GI), 3 (0.06%) were HIV positive, 208 (4.85%) had genital herpes, 120 (2.79%) had orchitis, 56 (1.30%) had non gonococcal urethritis (chlamydia were 19), and 1 (0.02%) had ophthalmia neonatorum. Conclusions Mode of transmission of STIs in this region is mainly by heterosexual contact and syphilis is the commonest followed by gonorrhoea. Keywords: Sexually Transmitted Infections, Hetrosexuality, Pattern, Sindh Province, Pakistan